2020
DOI: 10.1055/s-0040-1716726
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Abscesses and Fistulas in Infants and Children

Abstract: Perianal abscess (PA) and fistula-in-ano (FIA) are common entities in infancy. Although several hypotheses have been suggested, the pathogenesis of PA/FIA remains elusive. The natural course of these diseases in infancy is self-limiting in the majority of cases whereas older children show similarities to PA/FIA in adults. It is important to rule out rare differential diagnoses of PA/FIA such as inflammatory bowel disease (IBD), surgical complications after colorectal surgery, and immunodeficiencies. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
4
1
1
Order By: Relevance
“…Christison-Lagay et al in 2007 demonstrated that antibiotic use for perianal abscess decreased the likelihood of fistula formation. While 30.4% of the surgically treated group in this study developed complications mainly in a recurrent abscess or fistula formation, this was slightly higher than some other studies 8 .…”
Section: Resultscontrasting
confidence: 74%
“…Christison-Lagay et al in 2007 demonstrated that antibiotic use for perianal abscess decreased the likelihood of fistula formation. While 30.4% of the surgically treated group in this study developed complications mainly in a recurrent abscess or fistula formation, this was slightly higher than some other studies 8 .…”
Section: Resultscontrasting
confidence: 74%
“…It has traditionally been treated surgically by incision and drainage (ID) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, in the past two decades, some studies have shown that the conservative management appears to be effective in selected cases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the other hand, the other studies have recommended that the surgical procedure should involve a careful identification for the fistula and treatment of that by fistulotomy (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…As the authors mentioned, the antimicrobial therapy is mostly needed besides the local anti-inflammatory treatments. Further management strategies may be needed in some specific clinical conditions such as immune deficiency and inflammatory bowel diseases (IBD) [2]. However, specific cases including immune deficient ones, which are the most difficult to treat, were excluded from the study.…”
Section: Dear Editormentioning
confidence: 99%